2020
DOI: 10.1177/1044207320934800
|View full text |Cite
|
Sign up to set email alerts
|

High School Students With Emotional and Behavioral Disorders Perceptions of School Climate

Abstract: Students with emotional and behavioral disorders (EBDs), particularly those in high school, present myriad challenges for educators. Although research suggests that students with EBDs experience schooling differently than their peers, few studies have examined differences in perceptions of school climate. School climate is a multidimensional construct consisting of students’ perceptions of physical and social school environments. To address this gap, we leveraged school climate data from more than 350,000 high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Of these studies, three provided information regarding the types of disabilities that were represented in their sample (Jones & Bodtker, 1999; Rifenbark et al, 2021; Sakiz, 2017). Five studies specifically analyzed school climate perceptions of students with emotional and behavioral disorders (EBD; Collins et al, 2022; Gage et al, 2021; La Salle et al, 2018; Marsh et al, 2019; Ryabov, 2020), and one study interviewed students with intellectual disability (ID; Lopez et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these studies, three provided information regarding the types of disabilities that were represented in their sample (Jones & Bodtker, 1999; Rifenbark et al, 2021; Sakiz, 2017). Five studies specifically analyzed school climate perceptions of students with emotional and behavioral disorders (EBD; Collins et al, 2022; Gage et al, 2021; La Salle et al, 2018; Marsh et al, 2019; Ryabov, 2020), and one study interviewed students with intellectual disability (ID; Lopez et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…No studies reported information for transgender or non-binary identifying students. Four studies reported the race/ethnicity of their sample, which included students who identified as Black (4294; 49%), White (3178; 36%), Latinx/Hispanic (887; 10%), Asian/Pacific Islander (59; 1%), Native American (51; 1%), two or more race/ethnicities (154; 2%), and other (145; 2%; Collins et al, 2022; Gage et al, 2021; La Salle et al, 2018; Rifenbark et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with EBD are less engaged in school than their peers (Gage et al, 2021) and demonstrate poor social competence (Gresham, 2015). As such, practices associated with increased performance in these domains for students with EBD may hold promise for improving concomitant short-term outcomes (e.g., academic performance) and reduce long-term negative consequences (e.g., school dropout).…”
Section: School Engagement and Social Competencementioning
confidence: 99%
“…Many studies have found that SWDs had a variety of negative school climate perceptions, such as lower perceptions of feeling welcome and higher perceptions of bullying and harassment than GENs, with additional heterogeneity based on disability classification (Stiefel et al, 2018), lower emotional inclusion and academic self-concept than GENs (DeVries et al, 2018), and lower perceptions of school climate than GENs for students with emotional and behavioral disorders (Gage et al, 2020;Salle et al, 2018. In addition, researchers have published many studies documenting bullying and victimization of SWDs, or specific classifications of SWDs, which, while not reporting on SWD perceptions, might be linked to negative perceptions of these aspects of school climate (American Educational Research Association, 2013; Espelage, 2015;Gil & da Costa, 2010;Maag & Katsiyannis, 2012;Rose et al, 2009;Whitney et al, 1994). SWD academic performance is generally lower than that of their GEN peers (NCES, 2019b), and this also may result in negative perceptions of academic climate.…”
Section: Swds' Perceptions Of School Climate (Rq3)mentioning
confidence: 99%